Identifikasi Kendala Guru Berlatar Pendidikan Non IPA Terpadu dalam Membelajarkan IPA di SMP - Rohmah, Yustiani; Rinanto, Yudi; Mulyani, Sri (Universitas Sarjanawiyata Tamansiswa, 2023)
The purpose of this study is to find out and classify what are the obstacles for teachers with an integrated non-science educational background in teaching science at SMP Negeri 1 Bonorowo for the 2020/2021 academic year. This research is a qualitative descriptive study with the research subjects of three teachers of science subjects. Data collection techniques using questionnaires, interviews, and documentation. Data validity uses triangulation of data collection techniques, audit trails, and direct data collection by researchers. The validity of the instrument uses the validity of the language. The data analysis used is the Miles and Huberman model. The results of the study show that the obstacle for teachers with an integrated non-science educational background in teaching science at SMP Negeri 1 Bonorowo for the academic year 2020/2021 is a component in learning planning, namely an indicator component in the form of sentence composition. The components in the implementation of learning are the teacher component in the form of teacher educational background and a sense of laziness, the student component in the form of the special character of the student, the curiosity to ask questions, and the ability to analyze, the component of the learning material in the form of material that is not the teacher's educational background, the method and model components ( strategy) learning in the form of running out of time and adjusting learning methods and models, as well as facilities and infrastructure components in the form of a science laboratory shortage.